Plasma soluble CD163 is associated with postmortem brain pathology in human immunodeficiency virus infection. (24th April 2017) - Bryant, Alex K.; Moore, David J.; Burdo, Tricia H.; Lakritz, Jessica R.; Gouaux, Ben; Soontornniyomkij, Virawudh; Achim, Cristian L.; Masliah, Eliezer; Grant, Igor; Levine, Andrew J.; Ellis, Ronald J.
Abstract : Objective: Higher plasma soluble cluster of differentiation (CD)163 (sCD163), shed by monocytes and macrophages, correlates with neurocognitive impairment in HIV infection. We hypothesized that higher antemortem plasma or cerebrospinal fluid (CSF) sCD163 would be associated with greater postmortem neurodegeneration and/or microgliosis. Design: Retrospective, postmortem observational study. Methods: We measured sCD163 levels in antemortem plasma ( n  = 54) and CSF ( n  = 32) samples from 74 HIV-seropositive participants (median 5 months before death) who donated their brains to research at autopsy. Postmortem, we quantified markers of synaptodendritic damage (microtubule-associated protein 2, synaptophysin), microgliosis [human leukocyte antigen DR (HLA-DR), ionized calcium-binding adaptor molecule 1], astrocytosis (glial fibrillary acidic protein), and impaired protein clearance (β-amyloid) in frontal cortex, hippocampus, putamen, and internal capsule. Multivariable least-squares regression was used to evaluate the association between plasma or CSF sCD163 and histological measures, correcting for multiple comparisons. Results: Higher plasma sCD163 was associated with lower microtubule-associated protein 2 in frontal cortex [ B  = −0.23, 95% confidence interval (CI) −0.41 to −0.06, P  = 0.04], putamen ( B  = 0.32, 95% CI −0.52 to −0.12, P  = 0.02), and hippocampus ( B  = −0.23, 95% CI −0.35 to −0.10, P  = 0.01), and with lower synaptophysin in hippocampus ( B  = −0.25, 95% CI −0.42 to −0.03, P  = 0.02) but not putamen or frontal cortex ( P  > 0.05). Higher plasma sCD163 was associated with higher HLA-DR in putamen ( B  = 0.17, 95% CI 0.08 to 0.26, P  = 0.008). CSF sCD163 was not associated with any histological measure ( P  > 0.05). Conclusion: Higher plasma sCD163 in life is associated with greater synaptodendritic damage and microglial activation in cortical and subcortical brain regions.